Discontinuation of tenofovir disoproxil fumarate from initial ART regimens because of renal adverse events: An analysis of data from four multi-country clinical trials. - McNeil Ngongondo; Justin Ritz; Michael D Hughes; Mitch Matoga; Mina C Hosseinipour; AIDS Clinical Trials Group A5208, A5221, A5175 and A5274 Study Teams (Public Library of Science (PLoS), 2024)
Tenofovir disoproxil fumarate (TDF), a potent and commonly used antiretroviral drug, is associated with renal tubular dysfunction and renal adverse events. We evaluated the frequency of, time to, and baseline risk factors for discontinuing TDF from initial antiretroviral therapy (ART) regimens because of renal adverse events from presumed tenofovir renal toxicity. We conducted an observational cohort study as a secondary analysis of data from four clinical trials conducted mainly in low- and middle-income countries. We included ART naïve participants living with HIV who started TDF-containing ART regimens in the trials. Participants had to have estimated creatinine clearance (eCrCl) equal to or greater than 60ml/min before starting ART. The primary outcome was the first instance of discontinuing TDF because of renal adverse events attributed to tenofovir renal toxicity during the first 48 weeks after starting ART. We evaluated the cumulative incidence of discontinuing TDF and associated risk factors using Fine and Gray competing risk regression models with a backward elimination variable selection strategy. There were 2802 ART-naïve participants who started TDF-containing ART from the four clinical trials were included in the analysis. Fifty-eight percent were female, the median age was 34 years, and 87% had CD4 cell counts less than 200 cells/μl. Sixty-four participants (2.4%, 95% CI 1.7%-2.8%) discontinued TDF due to renal adverse events. Among the 64 participants, the median time to discontinue TDF was 9.4 weeks (IQR: 3.4-20.7 weeks). From multivariable Fine and Gray regression models, risk factors for discontinuing TDF were older age, CD4 cell count <200 cells/μl, presence and severity of anemia, and eCrCl <90 ml/min. The risk of discontinuing TDF because of renal adverse events was low in participants initiating TDF-containing ART with advanced HIV and normal renal function, attesting to the tolerability of TDF in ART in low- and middle-income countries.